2009
DOI: 10.1002/xrs.1170
|View full text |Cite
|
Sign up to set email alerts
|

Nanoresolution interface studies in thin films by synchrotron x‐ray diffraction and by using x‐ray waveguide structure

Abstract: In the last years we performed several measurements with synchrotron radiation of several facilities to reveal interesting interface phenomena on the nanoscale. We used both x-ray diffraction [1,2] (XRD) and spectrometry techniques. In this paper, we briefly summarize the results obtained from diffraction measurements, which lead us to our recent grazing incidence x-ray fluorescence analysis (GIXRF) and extended x-ray absorption fine structure (EXAFS) experiments.We show how a combination of experimental metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Takesada et al 483 compared MgGa 2 O 4 :Mn 2+ nano-phosphors with those made from ZnGa 2 O 4 :Mn 2+ to show that Mn 2+ was more homogeneously distributed within the Mg based nano-phosphur. Erdelyi et al 484 reported their depth profiling methods of a-Si/ Co/a-Si layers to give nano-resolution for the monitoring of Co/ Si inter-metallic phases. A combination of GIXRF and EXAFS with XSW enabled the authors to offer sufficient sensitivity and accuracy to monitor the production of the waveguide structures.…”
Section: Thin Films Coatings and Nano-materialsmentioning
confidence: 99%
“…Takesada et al 483 compared MgGa 2 O 4 :Mn 2+ nano-phosphors with those made from ZnGa 2 O 4 :Mn 2+ to show that Mn 2+ was more homogeneously distributed within the Mg based nano-phosphur. Erdelyi et al 484 reported their depth profiling methods of a-Si/ Co/a-Si layers to give nano-resolution for the monitoring of Co/ Si inter-metallic phases. A combination of GIXRF and EXAFS with XSW enabled the authors to offer sufficient sensitivity and accuracy to monitor the production of the waveguide structures.…”
Section: Thin Films Coatings and Nano-materialsmentioning
confidence: 99%
“…Erdelyi and coworkers have presented an overview of the work they have undertaken over the last few years which has covered techniques such as X-ray diffraction, GIXRF, and extended X-ray absorption fine structure (EXAFS). 304 They also described how GIXRF and EXAFS could be used in conjunction with X-ray standing waves to monitor the growth of the CoSi intermetallic phase by performing depth-profile measurements on amorphous silicon/ Co/amorphous silicon layers. The sensitivity and accuracy of the measurements were increased by placing the layers on a waveguide structure formed from two tantalum films.…”
Section: X-ray-based Applicationsmentioning
confidence: 99%
“…To improve the maximum count rate, Ohno et al proposed a new TES pixel design that had a new geometry of an absorber self-adjusting the operating temperature (18). In their first prototype, they fabricated TES pixels using a Au/Ti/ Au trilayer consisting of small heat sensors and a radiation absorption area and achieved a decay time constant of incident X-rays from an 55 Fe source of less than 20 µs. Rodrigues et al have been developing metallic magnetic calorimeters for enhancing the accuracy of atomic and nuclear data determination, in particular, X-ray and γ-ray emission probabilities (19).…”
Section: Detectionmentioning
confidence: 99%
“…That is, SQUID 2 acts as a low-noise preamplifier. The developed a mini-calorimeter offered an energy resolution of 40 eV for an 55 Fe source and 200 eV for an 241 Am source, respectively. As typically represented by roentgenograms, X-ray imaging using X-ray film has played an important role in the history of X-ray applications.…”
Section: Detectionmentioning
confidence: 99%